Read Aloud Goes to School Game Changer to Improve Literacy at Gurawan State Elementary School, Surakarta - Rahmawati, Widia Wahyu; Permadi, Aad Satria (Universitas Muhammadiyah Surakarta, 2025)
Indonesia faces a serious literacy crisis, as evidenced by the 2022 PISA data, which places the country at 70th out of 81 nations. The main challenges include low reading interest among children, limited access to quality books, and less effective teaching methods. This article explores the read aloud technique as a solution to enhance children's literacy through an engaging and interactive reading experience. This technique is discussed in the context of Albert Bandura's Social Cognitive Theory, which emphasizes the roles of observation, modeling, and reinforcement in the learning process. Through the Read Aloud Goes to School program at SD Negeri Gurawan, Surakarta, read aloud has not only succeeded in fostering a love for reading but also integrated literacy with education on global issues, such as climate change, using the book Keluarga Panik. This article concludes that read aloud is a game changer in efforts to improve literacy in Indonesia. With consistent implementation and community involvement, this technique holds great potential to create a generation of critical readers who care about the future. Keywords: Read Aloud, Literacy Crisis, Social Cognitive Theory